Case report: Chemotherapy plus sintilimab for the treatment of gastroesophageal junction hepatoid adenocarcinoma with liver metastasis: a case study with literature review - Lu, Genlin; Tu, Jiarui; Tu, Jinming; Jiang, Renya (Frontiers in Immunology, 2025)
ObjectiveTo elucidate the clinicopathological features and treatment of metastatic gastroesophageal junction hepatoid adenocarcinoma (GEJ HAC)using a case study and literature review.MethodsClinical presentation, results of histology and immunohistochemistry, and next-generation sequencing(NGS) in a patient with GEJ HAC metastasizing to the liver were reviewed. Chemotherapy (SOX or S-1) plus sintilimab was administered.ResultsA 65-year-old male patient with a history of hypertension was admitted to the hospital due to a one-week increase in serum AFP levels. There was a small intraluminal mass at the GEJ and a metastatic lesion in liver segment VIII, as well as enlarged perigastric and retroperitoneal lymph nodes. Tumor cells in both the GEJ and liver tissue exhibited a glandular shape with a nest-like adenoid structure. Immunohistochemical (IHC) analysis of the GEJ tissue showed positivity for AFP, CA19-9, CK7, CK20, MUC-1, P53 (wild type), Glypican-3, and HepPar-1, and negativity for Arginase-1, CD10, and Her-2. In the metastatic liver tissue, IHC testing demonstrated positivity for AFP, CD10, CK19, CK20, HepPar-1, MUC-1, Ki-67, and P53 (wild type), while CK7 was negative. The NGS report of GEJ mass indicated that the JAK2 and TP53 genes harbored missense mutations, while the MLH1, MSH2, MSH6, PMS2, ERBB2, EGFR, PIK3CA, APC, CTNNB1, CDH1, and DPYD genes were normal. The patient’s serum levels of CEA, CA19-9, and AFP were sharply decreased. The patient achieved a major pathological response (MPR) and remains in a progression-free stage.ConclusionsSintilimab-based chemotherapy has proven efficacy in achieving a MPR and maintaining a progression-free state for a patient with GEJ HAC that has metastasized to the liver.